Gaya kepimpinan Pengetua wanita dan hubungannya dengan stres guru di sebuah daerah di Johor Bahru - Krishnan, Kasthuri (2012)
The purpose of research was to investigate the style of leadership in Johor Bahru district and to find if there is any significant relations between the style of leadership of the principle from the teachers point of view and stress among teachers. This research was carried out by measuring the data gathered from the five point likert scale. The ‘Leader Behaviour Description Questionaire’ (LBDQ) measuring instrument was used to measure the dimension of principal’s leadership style, initiating structure and consideration. The teacher’s stress measuring instrument was used to measure the level of teachers’ stress based on principal’s leadership style form the dimensions mentioned above. A number of 124 teachers from five secondary schools from Johor Bahru were chosen for this research. They were chosen using randomly quota sampling. Data collection were analyzed by Statistical Package For Social Science(SPSS) Versiaon 12.0.The data collected were analysed based on descriptive and inferential statistic (frequencies, mean, standard devision, percentage, T-test, ANOVA and Pearson Correlation Coeffiecient). The outcome of the research showed that teachers were at high opinion of the principal, from both dimensions. Based on the research there was no significant differences between the teachers level of stress and their age, experiences, marital status, form teacher, teaching exam classes and the sessions they are teaching. However, there was a significant difference between teachers’ level of stress and their sex. There was a very weak negative relationship between structural dimension of principals leadership and teacher’s stress. There was no significant relationship between principal’s